2015
DOI: 10.14583/2318-7670.v03n01a03
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Físico-Químicos e Bioquímicos Durante o Armazenamento Refrigerado do Caqui em Atmosfera Modificada Passiva

Abstract: Recebido em agosto/2014; Aceito em dezembro/2014. RESUMO:Avaliou-se o comportamento físico-químico e bioquímico do caqui 'Rama Forte' armazenado sob refrigeração em condição de atmosfera modificada passiva. Utilizou-se frutos colhidos com coloração da epiderme amarelo alaranjado, sendo, após seleção, acondicionados em bandejas de poliestireno expandido, revestidas por filme plástico de polietileno de baixa densidade (10 µm de espessura) e armazenados à 7 ± 1ºC e 85 ± 5% de UR, avaliados a cada cinco dias duran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
1
0
4
Order By: Relevance
“…The value obtained for "Fuyu" persimmon fruit (5.33) in this study was lower than the one observed by Brackmann et al (2013) in Rio Grande do Sul, Brazil. The "Rama Forte" persimmon fruit in this study show similar results with the same crops growing in Jundiaí (São Paulo, Brazil) conditions (Mendonça et al, 2015). These results can be due to climate condition variations and experimental site, but could be also due to the fruit"s ripening stage and harvesting season.…”
Section: Yield and Physicochemical Fruit Characteristicssupporting
confidence: 79%
“…The value obtained for "Fuyu" persimmon fruit (5.33) in this study was lower than the one observed by Brackmann et al (2013) in Rio Grande do Sul, Brazil. The "Rama Forte" persimmon fruit in this study show similar results with the same crops growing in Jundiaí (São Paulo, Brazil) conditions (Mendonça et al, 2015). These results can be due to climate condition variations and experimental site, but could be also due to the fruit"s ripening stage and harvesting season.…”
Section: Yield and Physicochemical Fruit Characteristicssupporting
confidence: 79%
“…Decréscimo significativo no ângulo hue indica que a cor do produto se torna escura. A cor é um atributo importante na aparência comercial dos produtos vegetais, sendo um fator determinante no poder de aceitação de compra pelo consumidor (MENDONÇA et al, 2015). Apesar de ter ocorrido variação significativa nos valores de ângulo hue durante o armazenamento, visualmente não foi observada variação na coloração das raízes submetidas aos diferentes tratamentos, confirmando as informações obtidas nas demais variáveis analisadas sobre a cor do produto.…”
Section: Diasunclassified
“…The evaluation of vegetable conservation capacity has been performed to determine the efficiency of conservation methods concerning the protection of vegetables against oxidation and loss of commercial and nutritional value. The postharvest quality parameters used are physical, such as fresh mass loss, color and appearance, and chemical parameters such as soluble solids, pH and titratable acidity (Mendonça et al, 2015).…”
Section: Introductionmentioning
confidence: 99%